Effects of translaminar edge crack and fiber angle on fracture toughness and crack propagation behaviors of laminated carbon fiber composites - Asan, Ahmet Murat; Kaman, Mete Onur; Dag, Serkan; Erdem, Serkan; Turan, Kadir (Walter de Gruyter Gmbh, 2024)
In this study, the translaminar fracture toughness of carbon fiber laminated composites with different layer sequences was investigated experimentally and numerically for different crack directions. In the numerical study, first of all, the critical stress intensity factor was determined by using the M-integral method. Three-dimensional model and M-integral analysis were achieved in the ANSYS finite element package program. The non-local stress fracture criterion was used to in order to find failure curves of the materials. Then, in order to find the crack propagation directions numerically, the solid model was transferred to the LS-DYNA program and progressive failure analysis was performed. Fracture toughness decreased by 9.92 % with the change of crack angle from 15 degrees to 90 degrees. As the fiber angle changed from 0 degrees to 45 degrees, it decreased by 9.17 %. The biggest error between the experimental and numerical study results was found at alpha = 45 degrees, with a rate of 12.3 %.
Keywords: M-integral; Translaminar fracture toughness; Laminated composites; Progressive failure analysis